2019
DOI: 10.1109/tdmr.2019.2891949
|View full text |Cite
|
Sign up to set email alerts
|

Time Integration Damage Model for Sn3.5Ag Solder Interconnect in Power Electronic Module

Abstract: In this study, existing damage evolution models in the literature for solder layer in microelectronics have been reviewed. A two dimensional approximate semi-analytic time integration damage indicator model for Sn3.5Ag material solder interconnect in power electronic module has been proposed. The proposed time dependent damage model is dependent on the inelastic strain, the accumulated damage at previous time step and the temperature. The strains were approximated semi-analytically. A numerical modelling metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…Power components based on current packaging architectures are most susceptible to thermally induced fatigue damage of their wire bonds and the die attachment layer. While many studies contributed to the reliability modelling of PEMs [4][5][6][7][8], the informed deployment of these modules in different applications remains a challenge for the end-users. Driven by considerations for protecting intellectual property (IP), data on internal design and dimensions of power components and their bill of materials are not included in manufacturers' technical datasheets and thus are not readily available.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Power components based on current packaging architectures are most susceptible to thermally induced fatigue damage of their wire bonds and the die attachment layer. While many studies contributed to the reliability modelling of PEMs [4][5][6][7][8], the informed deployment of these modules in different applications remains a challenge for the end-users. Driven by considerations for protecting intellectual property (IP), data on internal design and dimensions of power components and their bill of materials are not included in manufacturers' technical datasheets and thus are not readily available.…”
Section: Introductionmentioning
confidence: 99%
“…Finite element (FE) modelling, coupled with lifetime prediction methodologies and models, offers a robust solution for this problem by predicting damage metrics for the expected failure modes, for example, the studies reported in [5][6][7][8]. Lifetime prediction methodologies for PEM have been also extensively developed, with much of the effort on establishing accurate models predicting the wire bonds lifetime under accelerated active and passive temperature cycling conditions that qualify the device for the respective application load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature cycling loads make the die attachment and interconnection layers (commonly solder) and the wire bonds susceptible to failure under modes such as interfacial cracking and lift-off, receptively. Both solder interconnection layer damage modelling, for example [7,8], and wire bond lift-off failure simulations, for example [9,10], have received extensive attention in power electronics reliability studies.…”
Section: Introductionmentioning
confidence: 99%